Pengenalan Artificial Intelligences untuk Meningkatkan Kemandirian Belajar Siswa di MA Ma’arif NU Assa’adah Bungah Gresik - Triyana, Illah Winiati; Mahmudah, Wilda; Kurniawati, Yeva; Nisa, Roisatun; Jamaluddin, Muhammad; Victoria Nalurita, Ika (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
One of the problems in education in Indonesia is the lack of knowledge among students about the latest technology. One example is Artificial Intelligence (AI) technology, which, if applied by students, can increase their independence in learning. However, there are still many students who do not understand Artificial Intelligence technology and its application in the independent learning process. This is also the case for students at MA Ma'arif NU Aassa'adah. In response to this, the mathematics education study program at Qomaruddin University conducted a community service program by providing solutions in the form of an introduction to and training in the use of Artificial Intelligence technology for student independence in learning. The two Artificial Intelligence technologies introduced are Gemini and Photomath. With this community service program, it is hoped that students will be able to apply the use of Artificial Intelligence technology in the independent learning process, thereby increasing their independence in learning.